African Mango (Irvingia gabonensis) Extract for Weight Loss: A Systematic Review - McLendon, Amber N; Spivey, Justin; Woodis, C. Brock (Journal of Nutritional Therapeutics, 2013)
<!– [if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> Objective: The objective of this review is to assess the effectiveness and safety of African mango (Irvingia gabonensis) extract on weight loss in humans. Design: A systematic review of articles evaluating the effect of African mango, IGOB131, dikanut, bush mango or Irvingia gabonensis on weight and obesity was conducted. Population: Three randomized, controlled trials were identified and met criteria for inclusion in the review with a total of 214 subjects receiving Irvingia gabonensis at various doses alone or in combination with other dietary supplements versus placebo over a period of four to ten weeks. Results: All studies demonstrated a decrease in weight ranging from 4-12kg (p<0.05). Other measures of weight loss including body fat percentage (p<0.05) and waist circumference (p<0.01) were also significantly decreased by Irvingia gabonensis. Improvements were also seen in total cholesterol, low density lipoprotein and fasting blood glucose. Few adverse events were reported but include insomnia, flatulence and headache. Conclusions: Irvingia gabonensis demonstrates potential for significant weight loss of up to 12 kilograms in overweight and obese subjects over a period of 10 weeks with few reported adverse events. Larger studies including subjects from multiple countries for 6 to 12 months should be conducted to elucidate the long-term effects in various populations. <!–[endif] –>